2014
DOI: 10.1080/07294360.2014.911251
|View full text |Cite
|
Sign up to set email alerts
|

Retaining female postgraduates in academia: the role of gender and prospective parenthood

Abstract: Women remain under-represented in almost all academic levels at universities internationally, and previous evidence has suggested that women move out of the university system in increasing numbers as they progress from postgraduate study to an academic career. The current study aimed to explore the role of gender in the reports of study experiences and future career plans of Australian postgraduate research students (n = 249). Questionnaire data indicated women were significantly less likely than men to rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Interview data were analyzed by searching for clusters and themes within and across participants (Miles, Huberman, & Saldaña, 2014). Because research has suggested that subpopulations of graduate student parents may experience distinct types of role strain and role enhancement (Crabb & Ekberg, 2014;Moreau & Kerner, 2015;Myers-Wells et al, 2011), I also analyzed the data within and across groups such as mothers, fathers, international students, and single parents.…”
Section: Research Design and Methodologymentioning
confidence: 99%
See 4 more Smart Citations
“…Interview data were analyzed by searching for clusters and themes within and across participants (Miles, Huberman, & Saldaña, 2014). Because research has suggested that subpopulations of graduate student parents may experience distinct types of role strain and role enhancement (Crabb & Ekberg, 2014;Moreau & Kerner, 2015;Myers-Wells et al, 2011), I also analyzed the data within and across groups such as mothers, fathers, international students, and single parents.…”
Section: Research Design and Methodologymentioning
confidence: 99%
“…Students who are parents need to attend not only to endless graduate program requirements but also to the daily needs of their children. I posit that because they assume multiple demanding roles (Chesser, 2015;Crabb & Ekberg, 2014;Douglas & Michaels, 2004;Hays, 1996), graduate students with children may experience more intensified difficulties with stress, finances, and struggles unique to their intersecting identities, as compared to graduate students who are not parents (Grady et al, 2014). However, parenthood and graduate school may also provide benefits to graduate student parents in that these roles may buffer the stress of one another (Wolf-Wendel & Ward, 2006) and allow students to gain new insights into parenting (Estes, 2011), research (Dillon, 2012), teaching, and service.…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations